Buddhism in Central Asia II Practices and Rituals, Visual and Material Transfer - Kasai, Yukiyo; Sørensen, Henrik H. (Brill, 2022)
The ERC-funded research project BuddhistRoad aims to create a new framework to enable understanding of the complexities in the dynamics of cultural encounter and religious transfer in pre-modern Eastern Central Asia. Buddhism was one major factor in this exchange: for the first time the multi-layered relationships between the trans-regional Buddhist traditions (Chinese, Indian, Tibetan) and those based on local Buddhist cultures (Khotanese, Uyghur, Tangut) will be explored in a systematic way. The second volume Buddhism in Central Asia II-Practice and Rituals, Visual and Materials Transfer based on the mid-project conference held on September 16th-18th, 2019, at CERES, Ruhr-Universität Bochum (Germany) focuses on two of the six thematic topics addressed by the project, namely on "practices and rituals", exploring material culture in religious context such as mandalas and talismans, as well as "visual and material transfer", including shared iconographies and the spread of 'Khotanese' themes.